Political Economy and the spirit of Liberalism: the «Money» factor - Medina Labayru, Carlos (Pensamiento. Revista de Investigación e Información Filosófica, 2025)
Orthodox economics conceals the true essence of money. Instead of understanding money as an artificial construct of the intellectual order, such economics represents it as if it were a natural commodity. Here, the theory of money is fitted into a general notion of the market, as a simply given, virtuously self-regulating sphere of the social. However, I maintain that this naturalistic bias is not just to be seen as a theoretical position within the debates of economic science. More deeply considered, its background is implicit in the nominalist and Calvinist roots underlying liberal thought. In particular: the deep scepticism typical of modern ontology, as it undermines the claims of human reason to provide authoritative judgments of the good, transcendent of merely quantitative thinking.
Keywords: money; commodity; liberalism; Calvinism; nominalism